A gene which encodes a predicted protein kinase can restore some functions of the ras gene in fission yeast. - Nadin-Davis, S A (1988)
The ras1- mutation of the fission yeast Schizosaccharomyces pombe interferes with sexual differentiation by preventing conjugation and causing inefficient sporulation. From a gene library, we have isolated a gene, byr1+, which when in high copy number restores efficient sporulation to ras1- strains. byr1+ encodes a putative 340-amino acid protein product, the sequence of which strongly suggests that it functions as a protein kinase. Gene disruption experiments show that loss of byr1+ function does not interfere with mitotic growth but it completely prevents both conjugation and sporulation. byr1 is thus another important gene in the sexual differentiation pathway and we believe that at least part of ras1 function is to act directly or indirectly through byr1 to modulate protein phosphorylation.